2019
DOI: 10.1101/558940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic and epigenetic architectures of neurological protein biomarkers in the Lothian Birth Cohort 1936

Abstract: Although plasma proteins may serve as important markers of disease risk in neurological conditions, the molecular mechanisms responsible for inter-individual variation in plasma protein levels are poorly understood. In this study, we conducted genome-and epigenome-wide association studies on the levels of 92 neurological proteins to identify genetic and epigenetic loci associated with their plasma concentrations (n = 750). We identified 62 independent genome-wide significant loci for 37 proteins (P < 5.4 x 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…We extracted summary statistics of pQTLs for plasma proteins from nine different proteomic GWASs and pooled them together using METAL. (10)(11)(12)(13)(14)(15)(16)(17)(18)21) In total, 51,799 individuals were included in our analysis. All of the participating individuals are of European ancestry.…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…We extracted summary statistics of pQTLs for plasma proteins from nine different proteomic GWASs and pooled them together using METAL. (10)(11)(12)(13)(14)(15)(16)(17)(18)21) In total, 51,799 individuals were included in our analysis. All of the participating individuals are of European ancestry.…”
Section: Data Sourcementioning
confidence: 99%
“…Therefore, they could serve as an important source of biomarkers (8). Recently, several genome-wide association studies (GWASs) of plasma proteins have identified protein quantitative trait loci (pQTLs) for thousands of plasma proteins (10)(11)(12)(13)(14)(15)(16)(17)(18). A pQTL is an association of protein levels at a genetic locus and is represented by the strongest associating single-nucleotide polymorphism (SNP) (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in proteomics have since opened up the possibility to investigate the association of genomic variants with protein abundances . Studies using aptamer‐, immunoassay‐, or mass‐spectrometry‐based proteomics have shown how changes in protein abundance can be associated with variants both in cis and in trans. Notably, such proteome‐wide screens of pQTL have been conducted in yeast, mice, maize, human cell lines, and primary cell lines .…”
Section: Understanding the Phenotypic Effects Of Variants In Genome‐wmentioning
confidence: 99%
“…Compared with observational studies, MR can avoid environmental confounders and reverse causality because the genetic variants used in MR cannot be easily changed by the external environment (8). Several genome-wide association studies (GWASs) of plasma proteins have recently identified the cis-variant in the protein-encoding gene (known as the protein quantitative trait loci, pQTL) for thousands of plasma proteins (9)(10)(11)(12)(13)(14)(15). Consequently, cis-pQTLs have been widely used as genetic instruments to estimate the causal effects of plasma proteins on complex diseases, satisfying three key assumptions of MR (relevance, independence, and exclusion assumptions) (16).…”
Section: Introductionmentioning
confidence: 99%